Building creativity: an argument for the reformulation of Brazil’s Copyright system - Magrani, Eduardo; Ferreira Matos, Helena (Brazilian Journal of Operations & Production Management, 2018)
Brazil has had a history of maximization of copyrights since the first rules prohibiting unauthorized uses of intellectual works emerged in the first half of the nineteenth century. The country’s current system of exceptions and limitations is not adequate to the current times, and has been applied in a restrictive manner. This has created an environment that is overly hostile to the use of works that would otherwise be considered fair, and hampers the development of a thriving creative economy. With this in mind, the reinterpretation of the norms regarding copyrights, as well as the reform of Copyright Law is requested.